Voltammetric Detection of Catecholamine Metabolites Using Tröger's Base Modified Electrode. Issue 4 (12th January 2018) - Shishkanova, Tatiana V.; Broncová, Gabriela; Fitl, Přemysl; Král, Vladimír; Barek, Jiří
Abstract: The advantage of surface modification of voltammetric sensor for determination of catecholamine metabolites such as vanillyl mandelic acid (VMA) and homovanillic acid (HVA) is discussed. The amino‐substituted coumarin derivative of Tröger's base was deposi‐ted on a graphite screen‐printed electrode (poly(CTB)/G/SPE) cycling the electrode potential between 0 and 1.2 V in 5 mL CH2 Cl2 containing 1×10 −3  mol L −1 tetrabutylammonium tetrafluoroborate and 20 μL 0.1 mol L −1 HCl. The poly(CTB) functions as both a selective recognition and pre‐concentrator agent for catecholamine metabolites. The high sensitivity of the voltammetric sensor coated by a poly(CTB) film toward VMA was achieved despite the high structural similarity between the two tested metabolites. We presume the voltammetric detection of these species is based on selective binding by a poly(CTB) film supported by its good adherence to the electrode substrate. The voltammetric signals of VMA were observable in the concentration range 10–100 μmol L −1 (LOD=0.2 μmol L −1 ) and 20–60 μmol L −1 (LOD=10 μmol L −1 ) in the model and synthethic urine samples, respectively. Abstract :